The Effect of Work Discipline and Employee Competence on Employee Performance with Organizational Commitment as an Intervening Variable (Study on Employees of the Pratama Pati Tax Office) - Andrias Irwanto; Mamik Indaryani; Joko Utomo (Formosa Journal of Science and Technology, 2023)
This study analyzes the effect of work discipline and competence on employee performance with organizational commitment as an intervening variable. The research data uses primary data in the form of a questionnaire. The population in this study were 156 employees with the method of determining the sample using the haier sampling formula and obtained a sample of 120 respondents. The data analysis used in this study is a structural equation model. The results of this study state that work discipline and competence have a positive effect on organizational commitment. The results of this study also state that work discipline, competence and organizational commitment have a positive effect on employee performance.